2016
DOI: 10.4040/jkan.2016.46.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Learning Activities on Application of Learning Portfolio in Nursing Management Course

Abstract: Purpose: This study was conducted to examine effects of a learning portfolio by identifying the learning of nursing students taking a learning portfolio-utilized nursing management class. Methods: A non-equivalent control group pretest-posttest design was used. Participants were 83 senior students taking the nursing management course in one of the Departments of Nursing at 2 Universities. Experimental group (n=42) received a learning portfolio-utilized nursing management class 15 times over 15 weeks (3 hours w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…En 55 % de las investigaciones se utilizaron las estrategias: aprendizaje basado en problemas, estudios de caso o la problematización como metodología para la enseñanza y aprendizaje de la asignatura de gestión, ya sea en la práctica [17][18][19][20] o en la teoría [21][22][23][24][25][26] . De estos, dos artículos agregaron el aprendizaje basado en lecturas 21 y juego de roles 24 como otras estrategias de enseñanza, mientras que 11 % usó el portafolio de evidencia en el aprendizaje autodirigido 27,28 . Únicamente 6 % utilizó la simulación con juegos de rol 29 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…En 55 % de las investigaciones se utilizaron las estrategias: aprendizaje basado en problemas, estudios de caso o la problematización como metodología para la enseñanza y aprendizaje de la asignatura de gestión, ya sea en la práctica [17][18][19][20] o en la teoría [21][22][23][24][25][26] . De estos, dos artículos agregaron el aprendizaje basado en lecturas 21 y juego de roles 24 como otras estrategias de enseñanza, mientras que 11 % usó el portafolio de evidencia en el aprendizaje autodirigido 27,28 . Únicamente 6 % utilizó la simulación con juegos de rol 29 .…”
Section: Resultsunclassified
“…En dos estudios se demostró su eficacia para el desarrollo de habilidades de gestión. Uno de ellos, realizado por Leal, en Brasil 27 , el otro por Choi 28 , en Corea, quienes concluyen que el uso de esta herramienta estimula habilidades del uso de la información en la recolección y el análisis. Asimismo, mejora las habilidades analíticas como la planificación y organización de recursos materiales y humanos.…”
Section: Portafoliounclassified
“…Garrett et al (2013), evaluating the implementation of an electronic portfolio to evaluate clinical competencies in the undergraduate course of nursing, showed that the method is useful in improving the competencies of nursing students [ 59 ]. Choi et al (2016) found that educational activities using a portfolio can increase personal focus and the ability of nursing students to better learn and update information [ 60 ]. These results were consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, reports have discussed the use of portfolios in nursing education (Sakajo et al., 2013; Park and Byun, 2014; Choi and Kim, 2016). Although these are introduced in lectures and exercises, their effects can also be obtained via introduction in practical training, as seen from the results for School A in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The cultivation of these skills is also an urgent challenge for basic nursing education, necessitating the search for ways to train students who are able to solve their own problems and apply things they have learned (Ministry of Health, Labor and Welfare in Japan, 2011; Korean Accreditation Board of Nursing Education, 2012; Unesawa et al., 2012; Choi and Kim, 2016). However, it has been difficult to achieve this because recent nursing students tend to be socially immature because of their limited life experiences, insufficient mastery of social norms, and poor communication skills (Ministry of Health, Labor and Welfare in Japan, 2011).…”
Section: Introductionmentioning
confidence: 99%